PRINCIPLE OF POLYSCALE OF GEOІNFORMATIONAL MONITORING OF URBAN ENVIRONMENT - Mikhno, O.; Patrakeyev, I.; Levinskova, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article is a continuation of series of publications that consider tactical properties of geoinformational monitoring of urban environment, which is a necessary component of modern military-geographical description of theater of operations. The property of polyscale allows to reveal spatio-temporal features of development of urban environment at different territorial levels - global, regional, local, as well as at the macro and meso level. Theoretical-set representation of the principle of polyscale modeling of urban objects is considered, on the basis of which models and methods of geoinformational monitoring at each scale level can be presented as a composition of ordered pairs of different structural type. An example of a hierarchy of methods and models used in urban studies is given. The concepts of basic models-compositions are introduced and the technology for construction of polyscale compositions is offered, which allow to determine the computational essence of corresponding mathematical models at each level of polyscale approach in studying of urban environment. Generalized scheme of application of principle of polyscale decomposition of geoinformational monitoring object of urban environment with definition of models of object of monitoring at each level of information space is developed. Each level of observed territory in the language of category theory can be interpreted as a category, the objects of which are spatial data, which are organized in the form of thematic layers (vector and raster) and contain many spatial objects grouped by thematic proximity and in certain coordinate system generalized for thematic layers. The proposed system of urban environment monitoring allows to improve principles of management decisions in development programs of different scales.